Pengaruh Persepsi Nasabah dan Tingkat Margin terhadap Keputusan Nasabah Pembiayaan Murabahah - Faisal Rakhman; Siska Devi Amalia (Masoem University, 2023)
The lack of understanding of customers about margins has led to customer perceptions that margins at Islamic banks are the same as interest at conventional banks. The level of margin that is considered high and not in accordance with the customer's ability is also thought to influence the customer's decision to murabahah financing. This study aims to determine how much influence customer perceptions and influence margin levels have on customer decisions on murabahah financing at BSI KCP Bandung Geger Kalong. The object of research is murabahah financing customers. The method used is associative quantitative. The type of data used is primary data which is processed using statistical applications, as well as using data collection techniques in the form of observation, interviews, questionnaires, and literature study. The population is murabahah financing customers in 2021 with a sample of 93 people.